Hyperpolarizing inhibition develops without trophic support by GABA in cultured rat midbrain neurons - Titz, Stefan; Hans, Michael Andreas; Kelsch, Wolfgang; Lewen, Andrea; Swandulla, Dieter; Misgeld, Ulrich (The journal of physiology, 2003)
During a limited period of early neuronal development, GABA is depolarizing and elevates [Ca2+]i, which mediates the trophic action of GABA in neuronal maturation. We tested the attractive hypothesis that GABA itself promotes the developmental change of its response from depolarizing to hyperpolarizing (Ganguly et al. 2001). In cultured midbrain neurons we found that the GABA response changed from depolarizing to hyperpolarizing, although GABAA receptors had been blocked throughout development. In immature neurons prolonged exposure of the cells to nanomolar concentrations of GABA or brief repetitive applications of GABA strongly diminished the elevation of [Ca2+]i by GABA. As revealed by gramicidin perforated-patch recording, reduced [Ca2+]i responses were due to a diminished driving force for Cl−. This suggests that immature neurons do not have an efficient inward transport that can compensate the loss of cytosolic Cl− resulting from sustained GABAA receptor activation by ambient GABA. Transient increases in external K+, which can induce voltage-dependent Cl− entry, restored GABA-induced [Ca2+]i elevations. In mature neurons, GABA reduced [Ca2+]i provided that background [Ca2+]i was elevated by the application of an L-type Ca2+ channel agonist. This was probably due to a hyperpolarization of the membrane by Cl− currents. K+-Cl− cotransport maintained the gradient for hyperpolarizing Cl− currents. We conclude that in immature midbrain neurons an inward Cl− transport is not effective although the GABA response is depolarizing. Further, GABA itself is not required for the developmental switch of GABAergic responses from depolarizing to hyperpolarizing in cultured midbrain neurons.
Gesehen am 08.04.2021